Efek rasio latihan interval intensitas tinggi terhadap kebugaran fisik pada siswa SMP - Nenot'ek, Frislin Paskaliner Yonatan; Kristiyanto, Agus; Syaifullah, Rony (Universitas Nusantara PGRI Kediri, 2025)
Indonesian students continue to exhibit low levels of physical fitness. This condition highlights the need for effective interventions to improve students’ physical fitness. This study aims to analyze the effects of HIIT with 1:2 and 1:5 ratios on junior high school students’ physical fitness, as well as to examine the moderating roles of gender and self-efficacy in their training responses. A quantitative approach with a 2 × 2 × 2 factorial design was employed, involving 100 junior high school students in the East Amabi Oefeto Subdistrict, Kupang Regency. The intervention lasted for eight weeks, consisting of 16 sessions conducted three times per week. The instruments used were the National Physical Fitness Test (Tes Kebugaran Jasmani Nasional, TKPN) and the Generalised Self-Efficacy Scale. The data were analysed using ANCOVA statistical procedures. Results revealed that HIIT ratio, gender, and their interaction significantly influenced physical fitness (p < 0.05). Conversely, self-efficacy alone did not show a significant effect (p > 0.05), although it contributed to the three-way interaction. Overall, this study confirms that both 1:2 and 1:5 HIIT ratios effectively improve students' physical fitness, with the 1:2 ratio being slightly more effective. Teachers can implement short HIIT sessions (10–15 minutes) every week, adjusting the ratios and intensity according to students' individual characteristics and needs. Future research should expand the sample size, include additional psychological variables, and explore variations in HIIT duration and frequency to develop a more comprehensive and practical school-based training model.